Audit Delay and Its Determinants: Financial Characteristics, Audit Firm Size, and Going Concern - Pasaribu, Mhd Hasan; Erlina; Rini, Endang Sulistya (Cita konsultindo, 2026)
This study examines the effect of solvency, profitability, and public accounting firm (PAF) size on audit delay, with the going concern audit opinion as a moderating variable. The sample consists of property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Secondary data were obtained from annual reports, financial statements, and audit reports published by the IDX. Panel data regression analysis was conducted using EViews software. The results show that solvency, profitability, and PAF size have positive and significant effects on audit delay. Furthermore, the going concern audit opinion moderates the relationship between financial characteristics and audit delay with varying effects. Specifically, the going concern audit opinion weakens the effect of solvency on audit delay but is not statistically significant. In contrast, it significantly strengthens the positive effect of profitability on audit delay. Meanwhile, the moderating effect of the going concern audit opinion on the relationship between PAF size and audit delay is negative but insignificant. These findings highlight the importance of financial characteristics and auditor-related factors in explaining audit delay in the property and real estate sector.